The Numerical Simulation of Welding Residual Stress of Dissimilar Transparent Thermoplastics with MZA Powder Absorbent (Journal of Material Science and Technology Research, 2023)
Abstracts: There are residual stresses in the joint caused by swift temperature variation in the process of laser transmission welding with metal absorbent. However, the related forming process is hard to detect through experimental methods. Herein, a physical model is established to describe the evolution of stress during the welding of polyarylsulfone (PASF) and polycarbonate (PC). The evolution of heat stress and the forming of residual stress is analyzed through the method of heat-force sequential coupling. In this process, the condensate transition, metal powder deformation, and clamping forces are involved in the mathematical model of stress-strain. In this model, the stress history can be divided into n time intervals according to the principle of superimposed stresses. The results revealed a significant correlation between the thermal history and stress evolution. Furthermore, the maximum von-mises stress appeared at the time of 1.7 s, then there was a decreasing tendency and stabled at 9 s. The von-mises stress was considered as residual stress after that time and the related stress distribution was investigated. The findings of this study provide a comprehensive understanding of residual stress on the joint.